Simon Christian de Schröder Scabinus Prim. Civitatis Gedanensis. Nat. 29 Aug. 1662. Denatus 29. Mai 1725 / Wolffgang. - Wolfgang, Johann Georg (1662-1744) (1725)
Przedstawia portret stojący w ujęciu 3/4 Simona Christiana Schrödera.